Development of an Interactive Website based on Chemo-edutainment using Google Sites on Chemical Bonding Material - Untung, M; Dewi, Fatria; Sanova, Aulia (Indonesian Journal of Education and Mathematical Science, 2025)
The research aims to develop an interactive website based on Chemo-edutainment using Google Sites as a learning medium on chemical bonding material. This research was motivated by students low understanding of the abstract and complex concept of chemical bonds, as well as learning methods that still tend to be monotonous. A chemo-edutainment approach that integrates elements of education and entertainment can make learning more interesting and enjoyable. The research method used is research and development ( Research an Develoment ) with the Lee and Owens model (Analysis, Design, Development, Implementation, Evaluation). The Research results show that : (1) the website development process is carried out through the stages of needs analysis, media design, interactive content development, and implementation for students; (2) The Validation results from material and media experts show that the website is suitable for use in the “Very good” category, (3) Teacher assessments and student responses to the website show high enthusiasm, the majority of students feel helped in understanding the concept of chemical bonds through this media. Thus, chemo-edutainment based website have proven to be effective in increasing students motivation, interest in learning and understanding of chemical bonding material.